The effect of Google Classroom as online media in students’ writing in the post pandemic Covid-19 - Arri Kurniawan; Erlik Widiyani Styati (Journal of Research on English and Language Learning (J-REaLL), 2023)
One of the learning tools that can be utilized as media is Google Classroom. This study aims at finding out whether there was any significant different before and after using Google Classroom as online media in students’ writing during the COVID-19 pandemic. The researchers used only one group for the participants. There were 30 students involved in this study. An experimental research design, including a pretest and posttest, was used for this study. In collecting data, the researchers used writing test. The paired sample t-test was used in SPSS version 18 in analyzing the data. The result of the computation is .000 from the pair sample test which is less than the significance level .005. This result indicated that students could motivate students to pay attention in learning. The application helped students to memorize vocabulary lists in the examples they just learned. The usage of Google Classroom tools helped students to concentrate more on the writing training they get in class. The students utilized the Google Classroom to write better on their vocabulary and affect student activity and student skills in writing. Students easily submitted text writing using a variety of different images in it. Therefore, it is suggested that teachers can utilize this media to motivate students to write in class and therefore the students can enhance learning outcomes.